Optimization of enzymatic hydrolysis of red tilapia scales (Oreochromis sp.) to obtain bioactive peptides (2021)
ABSTRACT: The objective of this study was to optimize the conditions of enzymatic hydrolysis (type of enzyme, pH, temperature (T), substrate (S) and enzyme concentration (E)) to increase content of soluble peptides (P), antioxidant activities and degree of hydrolysis DH (%), in hydrolysates. Also, the effect of scaling up from a 0.5 L to a 7.5 L reactor, was evaluated. Hydrolysis was carried out for 3 h in a 500 mL reactor, with Alcalase1 2.4 L and Flavourzyme1 500 L enzymes. A second experimental design was then developed with S and E as factors, where DH, P and antioxidant activity, were response variables. The Alcalase1 2.4 L was the most productive enzyme, with optimal S and E of 45 g/L and 4.4 g/L, respectively. Its hydrolysates showed antioxidant activities with IC50 of 0.76 g/L, 12 g/L and 8 g/L for ABTS, FRAP and ICA, respectively. The scale up didn’t showed negative effect on the hydrolysis.